Student's awareness of and interest in learning information technology / Arizan Yusoff - Yusoff, Arizan (2000)
The revolution of Information Technology bring the great impact on our educational system simultaneously change everyone perspectives about the importance of computer technology in today's world. In short period of time, Information Technology provides a new space to communicate, and at the same time becomes the epicenter for information. The uses of information technology cancerously spread among the student thus make the knowledge of information technology crucially important for everybody. To live in new millennium means to know about information technology. Those who know nothing about information technology will left behind. In this competitive edge, every one is rushing to be the best. More we know about information technology better the chances for us to be the best. Realizing that information technology play the major role to shape the world, this project paper tries to discover the "awareness level" among the student about information technology. Lat but not least, this project paper hopefully will help the student to realize the important of information technology in student's learning process.